2004
DOI: 10.1007/s00442-004-1764-3
|View full text |Cite
|
Sign up to set email alerts
|

Warming chambers stimulate early season growth of an arctic sedge: results of a minirhizotron field study

Abstract: We examined the effects of passive open-top warming chambers on Eriophorum vaginatum production near Toolik Lake, Alaska, USA. During the 2002 growing season, chamber warming was consistent with the magnitude and seasonality observed in recent decades throughout northwestern North America. Leaf-growth rates were higher in late May and early June; maximum growth rates in each leaf cohort occurred earlier and peak biomass was observed 20 days earlier within the chambers. Consequently, plants within the chambers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 48 publications
7
78
2
1
Order By: Relevance
“…Our results and those of several recent studies (Nordstroem et al 2001;Renner− malm et al 2005;Sullivan and Welker 2005;Sullivan et al 2008) clearly demon− strate that, in the hydro−terrestrial environment of wet hummock meadows, the ef− fect of passive open−top warming chambers clearly depends upon microtopography. The dry tops of hummocks have completely different microclimatic conditions in comparison with wet hummock bases.…”
Section: Microclimatic Parameterssupporting
confidence: 83%
See 2 more Smart Citations
“…Our results and those of several recent studies (Nordstroem et al 2001;Renner− malm et al 2005;Sullivan and Welker 2005;Sullivan et al 2008) clearly demon− strate that, in the hydro−terrestrial environment of wet hummock meadows, the ef− fect of passive open−top warming chambers clearly depends upon microtopography. The dry tops of hummocks have completely different microclimatic conditions in comparison with wet hummock bases.…”
Section: Microclimatic Parameterssupporting
confidence: 83%
“…Immediately following snow melt in 2002, the differences in soil surface temperatures between warmed and ambient plots approached a maxi− mum of 1.5°C. Later, daily mean temperatures differed by only 0.84°C (Sullivan and Welker 2005).…”
Section: Microclimatic Parametersmentioning
confidence: 91%
See 1 more Smart Citation
“…Sullivan and Welker (2005) found that use of a 0.3 cm depth of field gave annual root production estimates consistent with calculations based on values in the literature for E. vaginatum (Chapin et al 1988). Therefore, a 0.3 cm depth of field was used to scale minirhizotron data in the present study.…”
Section: Minirhizotronssupporting
confidence: 83%
“…This supports our hypothesis that E. vaginatum ecotypes have been shaped by strong selection pressures and have a very limited capacity to respond to changes in environmental conditions. A previous warming experiment at Toolik Lake observed increased leaf production of E. vaginatum in response to warming (using a similar method) but only in the early season, after which no difference in growth rate was observed between warmed and control plants (Sullivan & Welker, 2005). It is therefore possible that we would have seen differences between treatments if warming was applied earlier in the season (mid‐May).…”
Section: Discussionmentioning
confidence: 87%